(untitled) (Research, Society and Development, 2020)
In recent years, with the growing awareness of environmental preservation and pollution control, interest in the use of natural fibers in polymer composites has increased significantly. However, vegetable fibers are highly hygroscopic and their use, when wet, in the manufacture of composites, strongly affects the properties of these materials. Seeking improvement to the drying process of vegetable fibers, this work presents an experimental study of the drying process of fibrous bodies with particular reference to sisal fibers (Agave sisalana variety). For this propose, drying experiments were carried out with sisal fibers with an average moisture content of 11.19% (d.b.). The fibers were subjected to oven drying with forced air circulation at 50, 60, 70, 80 e 90°C. Experimental results of drying and heating kinetics of the fibers were presented and analyzed. It was verified that the moisture loss and temperature kinetics of the sisal fibers were influenced by the drying temperature, being more accentuated in the higher drying air temperatures, and the moisture removal occurred in falling rate period. Aspects of the fiber quality after drying were also evaluated.